Women's oral health-related quality of life as a risk factor for TMD symptoms. A case-control study. Issue 2 (4th March 2023) - Filho, Jairton Costa; Vedovello, Silvia Amélia Scudeler; Venezian, Giovana Cherubini; Vedovello Filho, Mário; Degan, Viviane Veroni
ABSTRACT: Objective: To investigate the association between temporomandibular disorder (TMD) symptoms and women's oral health-related quality of life (OHRQoL).Methods : An observational case-control study was performed with 765 adult women aged 21.5 years on average. Oral Health Impact Profile (OHIP-14) assessed OHRQoL and determined the selection of cases and controls matched by age and marital status at a ratio of 1:4 (153 cases: 612 controls). American Academy of Orofacial Pain's self-explanatory questionnaire assessed the TMD symptoms. The TMD symptoms' impact on OHRQoL was analyzed, estimating the odds ratio with a 95% confidence interval. Results: Of the women, 86.9% in the case group, and 69.6% in the control group presented some TMD symptoms ( p < 0.05). Women with an impacted OHRQoL are 2.95 (95% CI:1.79–4.86) times more likely to report some TMD symptoms ( p < 0.05). Discussion: Women with a negative impact on OHRQoL are more likely to report TMD symptoms.